(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In digital technologies, a user profile is a virtual section that allows users to manage their personal information, usage history, and settings. It is widely used in educational platforms to individualize the learning process and enhance its efficiency. The structure of a user profile typically includes a login module, a control panel, personal information, security settings, and service statistics. These elements enable users to use services securely and conveniently, as well as customize settings according to their preferences.